2016
DOI: 10.1177/0305735616658957
|View full text |Cite
|
Sign up to set email alerts
|

Personality, uses of music, and music preference: The influence of openness to experience and extraversion

Abstract: The purpose of this study was to ascertain whether uses of music partially mediate the link between personality and music preference. Undergraduate students ( N = 122) completed the following scales: The Brief Big Five Inventory, The Uses of Music Inventory, The Short Test of Music Preference, The Life Orientation Test Revised, The Beck Depression Inventory, and the Perceived Stress Scale. Openness to experience positively predicted preferences for reflective-complex (RC; e.g., jazz/blues) and intense-rebellio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
49
3
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 31 publications
13
49
3
10
Order By: Relevance
“…We identified five dimensions (Intense, Unique, Sophisticated, Contemporary, and Mellow) that corroborated with the MUSIC model by Rentfrow et al [11]. The first dimension, Intense, characterized by loud, forceful, and energetic music, was consistent with previous studies [15,44,45]. The second dimension, Unique, comprised uncomplicated, unaggressive, soft music, consistent with the findings of different authors [14,46].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We identified five dimensions (Intense, Unique, Sophisticated, Contemporary, and Mellow) that corroborated with the MUSIC model by Rentfrow et al [11]. The first dimension, Intense, characterized by loud, forceful, and energetic music, was consistent with previous studies [15,44,45]. The second dimension, Unique, comprised uncomplicated, unaggressive, soft music, consistent with the findings of different authors [14,46].…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, data showed that Mellow styles (gospel, pop, romantic, and soundtracks) were more likely to be chosen among participants. This corroborated findings from Clark and Giacomoantonio [48], but it contrasted findings from some authors [14,16,45,49], who contended that rock styles are the most popular among adolescents. Aside from the musical features of Mellow styles, it is possible that their popularity among participants responded to two elements motivating the participants' choices.…”
Section: Discussionsupporting
confidence: 86%
“…In line with previous studies (Langmeyer et al, 2012; Liljeström et al, 2013), it became clear that the personality scale related to Intellect/Openness is one related to all music preferences dimensions, with the exception of Afro-American Music in this study. On the one hand, it has been found that Intellect/Openness correlates positively with styles considered more complex musically (e.g., Classic and Ethnic Music), rebellious (e.g., Rock Music) and exciting (e.g., Electronic Music) (Rentfrow and Gosling, 2003; Vella and Mills, 2016). On the other hand, a negative correlation was identified with styles defined as light music, characterized by their emotional content, less musical complexity and high connection to the mass media (e.g., Brazilian Mainstream Music) (Zweigenhaft, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, es importante señalar que la personalidad es aquello que hace único a los individuos de ambos sexos; los psicólogos la correlacionan con cinco dimensiones: la conciencia, el neuroticismo, la extraversión, la apertura y la amabilidad (Cherry, 2019). Al respecto, Vella & Mills (2017) reportaron una asociación entre la personalidad y las diferentes preferencias artísticas, lo que ha permitido a los profesionales de la psicología efectuar avances en explicar la dinámica del comportamiento humano, en lo relacionado con las preferencias musicales y la personalidad, sugiriendo formas de intervención mediante el uso adecuado de distintas terapias musicales. En igual sentido, Greenberg, Baron, Stillwell, Kosinski & Rentfrow (2015) demostraron una correlación entre el gusto musical y la personalidad, explicado ello desde la teoría de la empatización-sistematización, lo cual permite inferir que, dependiendo del tipo de cerebro, el individuo genera diferentes preferencias musicales; es así como los del tipo E prefieren escuchar música de tonalidades calmadas, con poca excitación, mientras que los de tipo S prefieren música estridente con gran excitación (Greenberg et al, 2015).…”
Section: Géneros Musicales | Revista Virtualunclassified